Adjuvant vs. salvage Radiation Therapy after Radical Prostatectomy: Role of Decipher® in the Era of Personalized Medicine - Nowroozi, Ali; Karimi, Amirali; Alilou, Sanam; Amini, Erfan (Urology Journal, 2021)
Prostate Cancer (PCa) is the most prevalent cancer in men. Radical Prostatectomy (RP) as a primary definitive treatment may be followed by adjuvant or salvage radiotherapy. However, there are some uncertainties about receiving immediate adjuvant radiation after RP in men with adverse pathological features versus early salvage radiation therapy. Decipher is a novel genomic classifier and almost all studies have confirmed Decipher as a reliable predictor of metastasis, recurrence and mortality. With the aid of Decipher, clinicians are able to determine the need for adjuvant versus salvage radiotherapy. Decipher has the potential to reduce decisional conflicts in clinical recommendations, and is cost-effective. However, further investigations are required to prove Decipher’s role in clinical outcome improvement in patients receiving Decipher-based course of treatment compared with those receiving usual care.